Optimisasi produksi biogas dari limbah lateks cair pekat dengan penambahan logam Optimization of biogas production from concentrated-latex effluent with addition of metals - Irma KRESNAWATY; I SUSANTI; . SISWANTO; . TRI-PANJI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2008)
Summary The treatment of concentrated-latex effluent process applied in the field presently, has not obtain optimum additional benefits. Besides that, the technology using ponding system needs wide area and causes air pollution that such a way caused conflicts with society. The application concept of clean industry: reuse, reduction, recovery and recycling, makes the possibilities to convert the effluent to be usefull products. One of the alternative effluent process is by utilizing it as the source of renewable energy, that is in the form of biogas as an alternative energy. The preliminary research showed that the use of spontaneous latex skim coagulation, the addition of 1% manure as source of seed, and leaf biomass as the source of carbon could increase the biogas production. This research was carried out to optimize biogas production by adding metal ion and to observe the parameters which influenced every stage of biogas production. At the beginning of the process, pH showed increasing due to the hydrolysis process that generally occured in acid condition, but it remained stable (6.6-7.7) in the next steps, whereas, the VFA value as well as BOD value tended to increase. COD value had fluctuative inclination caused by the conversion of organic compounds to produce biogas and the hydrolysis process of leaf biomass to organic compounds that decom-posed to further biogas. The best result of biogas production was showed by addition of Fe3+ with optimum concentration 0.50 mg/L effluent.